Assessing the feasibility of a weather index insurance for the semi-arid region of Brazil - Lavorato, Mateus Pereira (Universidade Federal de Viçosa, 2020)
Weather index insurance (WII) has long been advertised as a viable alternative to overcome issues related to crop yield insurance products like information asymmetry and high transaction costs. WII products were firstly developed to assist climate-vulnerable farmers from developing countries where establishing a well-structured crop insurance market is expressively difficult due to the poor transport infrastructure and the prevalence of sparsely distributed small-scale farms. In Brazil, the semi-arid region stands out as the one that concentrates the ideal conditions for the implementation of a WII product since it houses thousands of climate-vulnerable family farmers. Seen this, the present study investigated the feasibility of a WII product for the Brazilian semi-arid region. A multidisciplinary approach based on meteorological, econometric and actuarial tools were employed, generating three distinct but complementary chapters. Firstly, it was shown that aridification is indeed a major threat to the livelihood of the population of the Brazilian semi-arid region. Secondly, it was identified that crop yield responses to weather conditions considerably vary in space and that an expressive portion of analyzed municipalities proved to have a low level of basis risk. Thirdly, a WII product was designed, priced and evaluated, proving to be effective in decreasing farmers’ downside risk. It is concluded, therefore, that it would be indeed feasible to establish a WII product in the semi-arid region of Brazil. Keywords: Feasibility. Weather Index Insurance. Brazil.

O seguro paramétrico de índice climático (WII) é, há muito, propagandeado como uma alternativa viável para contornar os problemas relacionados ao seguro baseado em produtividade, como a assimetria de informações e os altos custos de transação. O WII foi inicialmente desenvolvido para ajudar os agricultores climaticamente vulneráveis residentes em países em desenvolvimento, onde o estabelecimento de um mercado de seguro rural bem estruturado é consideravelmente difícil devido à uma infraestrutura de transporte deficiente e à prevalência de pequenas propriedades esparsamente distribuídas. No Brasil, a região semiárida se destaca como aquela que concentra as condições ideais para a implantação de um produto WII por abrigar milhares de agricultores familiares climaticamente vulneráveis. Visto disso, o presente estudo investigou a viabilidade de um produto WII para o semiárido brasileiro. Para tanto, foi utilizada uma abordagem multidisciplinar baseada em ferramentas meteorológicas, econométricas e atuariais, dando origem a três capítulos distintos, porém complementares. Primeiramente, foi demonstrado que a aridificação é, de fato, uma grande ameaça à subsistência da população da região semiárida. Em segundo lugar, identificou-se que as respostas da produtividade agrícola às condições climáticas variam consideravelmente no espaço e que uma parcela expressiva dos municípios analisados apresentou um baixo risco de base. Em terceiro lugar, um produto WII foi projetado, precificado e avaliado, o qual provou ser eficaz na redução do risco enfrentado pelos agricultores. Conclui-se, assim, que seria de fato viável desenvolver um produto WII para o semiárido brasileiro. Palavras-chave: Viabilidade. Seguro Paramétrico de Índice Climático. Brasil.
Keywords: Seguro agrícola; Climatologia agrícola; Clima de regiões áridas; Estudos de viabilidade - Brasil; Economias Agrária e dos Recursos Naturais